2017
DOI: 10.4049/jimmunol.1600714
|View full text |Cite
|
Sign up to set email alerts
|

AIM2 Inflammasome Is Critical for Influenza-Induced Lung Injury and Mortality

Abstract: The absent in melanoma 2 (AIM2) inflammasome plays an important role in many viral and bacterial infections, but very little is known about its role in RNA virus infection, including influenza A virus (IAV). In this study, we have designed in vivo and in vitro studies to determine the role of AIM2 in infections with lethal doses of IAVs A/PR8/34 and A/California/07/09. In wild-type mice, IAV infection enhanced AIM2 expression, induced dsDNA release, and stimulated caspase-1 activation and release of cleaved IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 59 publications
1
83
1
1
Order By: Relevance
“…One study stated that AIM2 dampened detrimental inflammation in the lung microenvironment of mouse infected with IAV and that AIM2‐deficient mice had exacerbated immune responses to IAV . The other study reported that AIM2‐deficient mice infected with IAV infection had less lung tissue damage and improved survival . While these findings may seem contradictory, they both suggest that AIM2 can detect host‐DNA released in the context of viral infections.…”
Section: Aim2 Detection Of Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…One study stated that AIM2 dampened detrimental inflammation in the lung microenvironment of mouse infected with IAV and that AIM2‐deficient mice had exacerbated immune responses to IAV . The other study reported that AIM2‐deficient mice infected with IAV infection had less lung tissue damage and improved survival . While these findings may seem contradictory, they both suggest that AIM2 can detect host‐DNA released in the context of viral infections.…”
Section: Aim2 Detection Of Dnamentioning
confidence: 99%
“…Downregulation of AIM2 in SK‐N‐SH cells decreased pyroptosis upon infection with EV‐A71 and augmented viral replication . In contrast AIM2 did not control the replication of Influenza A virus (IAV) in murine models . However, mice lacking AIM2 had reduced lung inflammation and injury after (IAV) infection as illustrated by decreased inflammatory cells infiltrate and decreases lung tissue damage .…”
Section: Aim2 In Health and Diseasementioning
confidence: 99%
“…For example, host‐derived DNA molecules are liberated from virus‐infected cells and accumulate in the lungs following infection by the RNA virus IAV. A study has shown that that AIM2‐deficient mice infected with IAV exhibited attenuated lung injury and significantly improved survival compared with wild‐type mice . Another study, however, has reported that AIM2‐deficient mice had increased susceptibility to IAV infection, owing to increased numbers of infiltrating leukocytes and an exaggerated immune response .…”
Section: Aim2 Inflammasomementioning
confidence: 99%
“…This recognition leads to the activation of signaling pathways and the production and secretion of IFNs of type I (IFNα and IFNβ) and III (IFNλ2 or IL-28A, IFNλ3 or IL-28B, and IFNλ1 or IL-29), and chemokines and cytokines involved in inflammatory processes [50]. IAV RNAs are mainly recognized by the endosomal, membrane-associated PRR Toll-like receptors (TLRs) 3 (double-stranded RNAs, dsRNAs) or 7/8 (ssRNAs), respectively [50,51], by the cytoplasmic PRR retinoic acid-inducible gene I (RIG-I), which detects dsRNA and 5 -triphosphates of the negative ssRNA viral genome [50,52], generated during replication of multiple viruses, by the NOD-like receptor family member NOD-, LRR-and pyrin domain-containing 3 (NLRP3), which recognizes various stimuli (see below) [53] and by the absent in melanoma 2 (AIM2) protein, recognizing not well-characterized influenza stimuli [54]. The result of PRR detection of viral PAMPs is the activation of multiple transcription factors, such as the nuclear factor kappa β (NF-κB), the activator protein 1 (AP-1), and IFN regulatory factors (IRF)-3 and IRF-7, which are responsible for the transcription of IFNs [50,55,56] and pro-inflammatory cytokines [57].…”
Section: Innate Immunity In Iav Infectionsmentioning
confidence: 99%